Driving Germany : the landscape of the German Autobahn, 1930-1970 - Zeller, Thomas, 1966- (Studies in German history, 2006)
"Published in association with the German Historical Institute, Washington, D.C. Hitler's Autobahn was more than just the pet project of an infrastructure-friendly dictator. It was supposed to revolutionize the transportation sector in Germany, connect the metropoles with the countryside, and encourage motorization. The propaganda machinery of the Third Reich turned the Autobahn into a hyped-up icon of the dictatorship. One of the claims was that the roads would reconcile nature and technology. Rather than destroying the environment, they would embellish the landscape. Many historians have taken this claim at face value and concluded that the Nazi regime harbored an inbred love of nature. In this book, the author argues that such conclusions are misleading. Based on rich archival research, the book provides the first scholarly account of the landscape of the Autobahn"--